External debt, state ownership and technical efficiency: a stochastic frontier analysis of emerging economies - Yap, Woon Kan; Kamarudin, Fakarudin; Gryzelius, Jenny (Springer Nature, 2024)
Arguing that the litmus test of external debt sustainability should be based on total factor productivity growth instead of mere GDP growth, this study examines the effect of external debt on total factor productivity through technical efficiency change using the Stochastic Frontier Analysis method. To deepen the analysis, the dynamics of technical efficiency, public sector external debt and state ownership are also investigated in this study. The results show that external debt of the private sector increases total factor productivity by improving technical efficiency, whereas the contrary is true with regard to external debt of the public sector. Hence, between the public and private sectors, the latter shows greater efficiency in allocating and using external debt. Nonetheless, the negative impact of public sector external debt on technical efficiency can be mitigated by transferring state-owned assets to the private sector through privatization.